Whole genome sequencing and comparative genomics of Mycobacterium orygis isolated from different animal hosts to identify specific diagnostic markers - Karthik, Kumaragurubaran; Subramanian, Saraswathi; Vinoli Priyadharshini, Michael; Jawahar, Ayyaru; Anbazhagan, Subbaiyan; Kathiravan, Ramaiyan Selvaraju; Thomas, Prasad; Babu, Ramasamy Parthiban Aravindh; Gopalan Tirumurugaan, Krishnaswamy; Raj, Gopal Dhinakar (Frontiers in Cellular and Infection Microbiology, 2023)
The present study was carried out to isolate, whole genome sequence M. orygis from different animal species (cattle, buffalo and deer). Comparative genomics was also employed to identify molecular marker for the differentiation of M. orygis from other MTBC members. Isolation and whole genome sequencing of M. orygis was carried out for 9 samples (4 cattle, 4 deer and 1 buffalo) died due to tuberculosis. Comparative genomics employing 53 genomes (44 from database and 9 newly sequenced) was performed to identify SNPs, spoligotype, pangenome structure, and region of difference. M. orygis was isolated from water buffalo and sambar deer which is the first of its kind report worldwide. Comparative pangenomics of all M. orygis strains showed a closed pangenome structure which is also reported for the first time. Pairwise SNP between TANUVAS_2, TANUVAS_4, TANUVAS_5, TANUVAS_7 and NIRTAH144 was less than 15 indicating that the same M. orygis strain may be the cause for infection. Region of difference prediction showed absence of RD7, RD8, RD9, RD10, RD12, RD301, RD315 in all the M. orygis analyzed. SNPs in virulence gene, PE35 was found to be unique to M. orygis which can be used as marker for identification. The present study is yet another supportive evidence that M. orygis is more prevalent among animals in South Asia and the zoonotic potential of this organism needs to be evaluated.